2019
DOI: 10.1007/s12105-019-01026-0
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi–Fujimoto Disease and Prognostic Implications

Abstract: Kikuchi-Fujimoto disease (KFD) is a rare cause of lymphadenitis seen mostly in Asian populations (Kikuchi in Nippon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 15 publications
(18 reference statements)
0
29
1
8
Order By: Relevance
“…One 22 year old male patient in this study presented with symptoms of cervical lymphadenopathy for The histopathology findings of the excisional lymph node biopsy remains gold standard for confirming Kikuchi's disease. In this study, the findings were sub grouped into 3 morphological phases as done in previous studies 5,7,8 , and a vast majority of the confirmed cases presented in proliferative phase of KFD (n = 40, 59.7%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One 22 year old male patient in this study presented with symptoms of cervical lymphadenopathy for The histopathology findings of the excisional lymph node biopsy remains gold standard for confirming Kikuchi's disease. In this study, the findings were sub grouped into 3 morphological phases as done in previous studies 5,7,8 , and a vast majority of the confirmed cases presented in proliferative phase of KFD (n = 40, 59.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Clinically and histologically, the disease is often misdiagnosed as tuberculosis, lymphoma or systemic lupus erythematosus (SLE) 4 . KFD can be seen in patients with previous history of SLE, it can coexist with SLE or complicate into SLE 7 .This association with SLE was more common in Asian than European patients 6 . Meanwhile, a significant number of patients were found to have underlying viral infections 6 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations